URGENSI SANAD DALAM MENINGKATKAN PROFESIONALITAS GURU PENDIDIKAN AGAMA ISLAM - Muhammad Hamid; Syamsul Bakri (Al-Hasanah : Jurnal Pendidikan Agama Islam, 2023)
As technology develops, Islamic Religious Education teachers are challenged to further develop their intellectual abilities so they don't lose their role to digital technology. One of the best and most appropriate methods for Islamic Religious Education teachers to increase their knowledge is to study with teachers who are at a higher level or more experienced than them, or who are known as sanad ‘ilm in Islam. The purpose of this research is to explain its importance as one of the aspects that a teacher must have in order to become a professional teacher in his field. This study uses a literature approach (library research) and descriptive analysis in writing, so that the results of this study are in the form of an explanation of the collected library data. The results of this study explain that the method takes a sanad ‘ilm with the aim of increasing aspects of a teacher's knowledge, which is very important and has the basis of the arguments of the Koran and Hadith. It doesn't end there; even with a sanad ilm, the scientific knowledge of a teacher will at least get three benefits, namely: can improve intellectual aspects; scientific originality; objective in viewing; and principled in science.